Pengaruh Fluktuasi Harga Emas dan Strategi Pemasaran Tabungan Emas terhadap Minat Bertransaksi Nasabag di Mediasi dengan Situasi Pandemik pada Pegadaian Syariah Cabang Gorontalo - Asral Kelvin Sahrain (Scimadly Publishing, 2023)
This research was conducted at the Sharia Pawnshop Gorontalo Branch, aiming to find out 1). Does Gold Price Fluctuation (X1), and Gold Savings Marketing Strategy (X2) affect Customer Transaction Interest (Y2) mediated by Pandemic Situation (Y1) , at Pegadaian Syariah Gorontalo Branch The results showed that the two behavioral variables of Gold Price Fluctuations (X1), and the Gold Savings Marketing Strategy (X2) had a Positive and Significant Effect, which was indicated by a Fluctuation significance value of 0.00 less than 0.05 and a positive beta coefficient of 0.16. , the significance value of Marketing Strategy is 0.00 less than 0.05 which means it is significant and the beta coefficient is positive at 0.52 Furthermore, the two Gold Price Fluctuation variables (X1), and the Gold Savings Marketing Strategy (X2), together have a positive and significant effect mediated by the Pandemic Situation variable (y1) which is indicated by the direct influence of Gold Price Fluctuations on Customer Transaction Interest of 0.521 and the indirect effect of the Fluctuation variable on the Customer's Transaction Interest through the Pandemic Situation obtained the calculation results of 0.207 X 0.254 = 0.053 with a total effect of 0.441 and the direct influence of Marketing Strategy on Customer's Transaction Interest of 0.304 and the indirect effect of the Gold Savings Marketing Strategy variable on Customer's Transaction Interest through Situations Pandemic results obtained by the calculation of 0.293 X -0.254 = 0.074 with a total effect of 0.378